Polymer Network Stabilized Flexoelectric Polarization - Lachezar, Komitov; Hegde, Gurumurthy; Lee, Seung Hee (Patent Application Publication, 2013)
A liquid crystal device comprising a first substrate; a second substrate; and a liquid crystal layer sandwiched between the first substrate and the second substrate, the liquid crystal layer comprising a nematic liquid crystal material and a polymer network. The polymer network is anchored to said first substrate and is configured to alternatingly induce splay deformation and bend deformation of the nematic liquid crystal material along a line parallel with the first substrate. Hereby, the relaxation time τfall of the liquid crystal device is reduced.